Effect of Radiotheraphy on Impaired Aortic Elasticity and Stiffness in Patients With Breast Cancer. (August 2014) - Kilicaslan, Baris; Piskin, Gonul Demir; Susam, Ibrahim; Dursun, Huseyin; Ozdogan, Oner
We evaluated the effect of radiotherapy (RT) on the elastic properties of the aorta using echocardiography in patients with breast cancer (BC). A total of 105 women with left-sided epidermal growth factor receptor 2 ( erb-2 ) BC were divided into 2 groups, group 1 with patients who did not receive RT and group 2 with patients who received RT. In all patients, echocardiographic examination and serum high-sensitivity C-reactive protein (hs-CRP) levels were determined. A significant decrease in aortic distensibility (AD) and increase in hs-CRP were seen from group 1 to group 2. The AD was inversely correlated with left ventricle diastolic diameter, systolic blood pressure (SBP), left atrial diameter, age, and RT dose. The AD was significantly related to age, SBP, and RT dose. Increased RT dose is significantly correlated with impaired elastic properties that may contribute to the relation of RT and increased rate of cardiovascular events among patients with BC who received RT.